Sexist advertising of women car washers in the Andean mountains - Gutiérrez-Gómez, Edgar; Munaris-Parco, Sonia Beatriz; Moscoso-Paucarchuco, Ketty Marilú; Quispe-Rodríguez, Juan; Aspur-Barrientos, Jaime Carmelo (Frontiers in Sociology, 2025)
The struggle for gender equity is progressing positively; however, the Peruvian highlands, characterized by its predominantly macho characteristics, lags behind in achieving this equity. The study on sexist advertising in car wash centers in the Peruvian highlands was conducted based on participant observation and interviews with the main actors who display sexist advertising posters on public roads. The objective of this study is to analyze the sexist implications of advertising posters with images of young women in skimpy clothing, exposing their body parts in full color while sensuously bathing in water, soap, and shampoo foam. This serves as an advertising hook to attract male customers seeking car washing services. However, it is concluded that this form of illegal advertising and labor practice is deemed sexist, as it lacks prior control by local authorities and violates principles of individual privacy and ethics. Sexism in car washes in the Peruvian highlands reaffirms the macho behavior of both private and public car drivers.